2021
DOI: 10.3390/agriculture11060469
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effect of Application of the Herbicide S-Metolachlor on the Activity of Some Enzymes Found in Soil

Abstract: Herbicides are being used more and more to increase productivity in agriculture, but their excessive has been shown to lead to adverse effects on the environment, especially on the soil. Within this study the effect of the herbicide S-metolachlor on the activity of several enzymes (dehydrogenase, protease, phosphatase and urease) found in the loamy-clayey soil has been analyzed. There were seven experimental variants corresponding to the untreated soil and to the application of six distinct doses of S-metolach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
4
10
0
Order By: Relevance
“…A similar behavior has been noticed when the herbicide fomesafen has been used for the soil treatment [14]. The herbicide S-metolachlor revealed an inhibitory effect against dehydrogenase, the decrease in the activities the enzyme being dose-dependent [32]. Another herbicide, butachlor stimulated activity of dehydrogenase for soil under flooded conditions, but had a detrimental affect against dehydrogenase for un-flooded conditions [19].…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…A similar behavior has been noticed when the herbicide fomesafen has been used for the soil treatment [14]. The herbicide S-metolachlor revealed an inhibitory effect against dehydrogenase, the decrease in the activities the enzyme being dose-dependent [32]. Another herbicide, butachlor stimulated activity of dehydrogenase for soil under flooded conditions, but had a detrimental affect against dehydrogenase for un-flooded conditions [19].…”
Section: Discussionsupporting
confidence: 69%
“…A similar result indicating an increase in FA during 30-day incubation has been obtained when the herbicide fomesafen have been used [14]. Other studies have shown the inhibition of FA [32,74,75], respectively a stimulation of FA in samples of soil treated with other herbicides [22,60,71,76]. Application of the herbicide butachlor conducted to stimulation in the activity of phosphatase under un-flooded conditions and inhibition under flooded conditions [19].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations